Manuscripts and Philological Studies in Indonesia - Zainal Arifin Nugraha (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2023)
This essay is based on the fact that Indonesia is a country with abundant presence of ancient manuscripts. The manuscript is an ancient cultural heritage that contains various things about life in the past. Research on a manuscript aims to determine the history and culture of a nation and then to find the relevance of it with the present live. Furthermore, it can also be used in the future. Nowadays, the manuscript is one of the ten objects of Indonesian cultural advancement that has been set in the constitution, Article 5 Law Number 5 of 2017 concerning the Advancement of Culture. Therefore, it deserves to get more attention from many parties.